2022-RA-893-ESGO Is ethnicity a risk factor for differential outcomes in mucinous ovarian cancer? experience from a UK gynaecological oncology centre. (20th October 2022) - Olaoye, Tejumola; Subba, Kamana; Ganesan, Raji; Williams, Anthony; Boyle, William; Balega, Janos; Yap, Jason; Singh, Kavita; Sundar, Sudha
Abstract : Introduction/Background: Primary Mucinous Epithelial Ovarian Cancer (PMEOC) is a rare disease representing 3–4% of all ovarian cancers. PMEOC often presents early (65–80%) and has a good overall prognosis. Poor prognostic factors include infiltrative histological subtype, capsule rupture, and advanced stage. The Pan-Birmingham Gynaecological Cancer Centre (PBGCC) serves a large multi-ethnic population of 2 million people; 82.8% white ethnicity, 10.8% South-Asian ethnicity, 3.3% Black ethnicity, 2.4% Mixed ethnicity, 0.9% other ethnicity. We investigated whether ethnicity was a risk factor for differential outcomes in patients diagnosed with PMEOC. Methodology: Case notes of patients diagnosed with PMEOC at PBGCC between December 2005- February 2022 were retrospectively analysed. Data analysis was performed using Microsoft Excel. Results: All pathology was reviewed of the 160 cases identified to confirm PMEOC, 39 were excluded leaving 121 for data analysis. Patient ethnicities were: 17 (14%) South Asian, 85 (70%) white, 4 (3%) other, and 16 (13%) unknown. Age at diagnosis for the whole population was normally distributed with mean of 53.8 (±3) years. Age for non South Asian remained normally distributed with a mean of 55.7 (±3.1) years. However, a bimodal age distribution was noted in South Asian patients with two distinct groups- >40 and ≤ 40 years old with mean age at diagnosis being 55.4 (±4.1) and 25.1 (±8) years respectively. South Asian patients were more likely to be diagnosed with PMEOC ≤40 years old (p=0.01), stage 1C at diagnosis (p=0.03) and in women ≤40 more likely to have infiltrative histology (p=0.025). Conclusion: We have demonstrated that South Asian women under 40 appear to have a distinct high risk phenotype for PMEOC. Larger studies are required to confirm this as a novel risk factor and if confirmed work to elucidate biological causes is urgently needed.